Exploring the Origin and Relatedness of Maternal Lineages Through Analysis of Mitochondrial DNA in the Holstein Horse - Engel, Laura; Becker, Doreen; Nissen, Thomas; Russ, Ingolf; Thaller, Georg; Krattenmacher, Nina (Frontiers in Genetics, 2021)
Maternal lineages are important for the breeding decision in the Holstein horse breed. To investigate the genetic diversity of the maternal lineages and the relationships between founder mares, the maternal inherited mitochondrial genome (except the repetitive part of the non-coding region) of 271 mares representing 75 lineages was sequenced. The sequencing predominantly revealed complete homology in the nucleotide sequences between mares from one lineage with exceptions in 13 lineages, where differences in one to three positions are probably caused by de novo mutations or alternate fixation of heteroplasmy. We found 78 distinct haplotypes that have not yet been described in other breeds. Six of these occurred in two or three different lineages indicating a common ancestry. Haplotypes can be divided into eight clusters with all mares from one lineage belonging to the same cluster. Within a cluster, the average number of pairwise differences ranged from zero to 16.49 suggesting close maternal relationships between these mares. The results showed that the current breeding population originated from at least eight ancestral founder mares.